Self-regulated learning strategy in learning activities of literal reading course to build learning independence - Nurjanah, Ratih Laily (SALEE: Study of Applied Linguistics and English Education, 2023)
This study attempts to describe how a Self-regulated learning strategy is implemented in Literal Reading course learning activities based on the characteristics of each strategy phase: Forethought and Planning phase, Monitoring on Performance phase, and Reflection on Performance. This case-study research involves Literal Reading class as the lowest reading comprehension level. It is expected that the learning activities given in the activities meet the needs of reaching the objectives of Literal Reading and match the characteristics of each phase of the Self-regulated learning strategy. Forethought and Planning phase focuses on giving chances to students to get familiar with the materials by observing the learning objectives and plan on what they will do to reach the goals. Monitoring on the Performance phase works on how students can control their learning activities according to their preferences and strategies while allowing them to work with peers or have discussions with the lecturer. Reflection on Performance allows students to review any feedback or new information to plan better strategies in learning. The implications are discussed in the findings.